Stanisaw Brzozowski and the migration of ideas : transnational perspectives on the intellectual field in twentieth-century Poland and beyond - Kozicka, Dorota; Herlth, Jens; Swiderski, Edward M., 1948- (Lettre (Transcript (Firm)), 2019)
As a writer, critic, and philosopher, Stanislaw Brzozowski (1878-1911) left a lasting imprint on Polish culture. He absorbed virtually all topical intellectual trends of his time, adapting them for the needs of what he saw as his primary mission: the modernization of Polish culture. The essays of the volume reassess and contextualize Brzozowski's writings from a distinctly transnational vantage point. They shed light on often surprising and hitherto underrated affinities between Brzozowski and intellectual figures and movements in Eastern and Western Europe. Furthermore, they explore the presence of his ideas in twentieth-century century literary criticism and theory.